Proceedings 2016 Network and Distributed System Security Symposium 2016
DOI: 10.14722/ndss.2016.23390
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Mobile Web Users Through Motion Sensors: Attacks and Defenses

Abstract: Abstract-Modern smartphones contain motion sensors, such as accelerometers and gyroscopes. These sensors have many useful applications; however, they can also be used to uniquely identify a phone by measuring anomalies in the signals, which are a result of manufacturing imperfections. Such measurements can be conducted surreptitiously by web page publishers or advertisers and can thus be used to track users across applications, websites, and visits.We analyze how well sensor fingerprinting works under realworl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…( §5.1) -We carry out the first large-scale user study to evaluate the trade-off between privacy and utility of fingerprinting countermeasures. We evalute both our proposed countermeasure as well as the obfuscation technique proposed by Das et al [16] and find that users experience no significant ill effects from the countermeasures. ( §5.3)…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…( §5.1) -We carry out the first large-scale user study to evaluate the trade-off between privacy and utility of fingerprinting countermeasures. We evalute both our proposed countermeasure as well as the obfuscation technique proposed by Das et al [16] and find that users experience no significant ill effects from the countermeasures. ( §5.3)…”
Section: Introductionmentioning
confidence: 99%
“…In turn, advertisers have started using browser fingerprinting [9,19,29] to track users across the web without the use of cookies. As the battleground shifts to mobile platforms, which are quickly becoming the dominant mode for web browsing [1,5,6,8], existing fingerprinting techniques become less effective [22,36]; at the same time, new threats emerge: mobile browsers give web pages access to internal motion sensors (accelerometers and gyroscopes) and researchers have showed that imperfections in these sensors can be used to fingerprint smartphones [16,18,22], boosting the accuracy of a weakened browser fingerprint.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations